The gut microbiota in liver transplantation recipients during the perioperative and postoperative recovery period - Bai, Zhongyuan; Wang, Yan; Li, Yaoping; Xu, Jun; Lai, Zhiyong (Frontiers in Microbiology, 2025)
BackgroundChronic Liver Disease (CLD) is one of the frequent causes of death, especially in the developing world. Liver transplantation (LT) is an effective modality to treat end-stage liver disease. Perioperative management of liver transplantation patients and prevention of postoperative complications are the key to improving patient prognosis and quality of life, and the intestinal flora of these patients can affect postoperative complications and overall prognosis.MethodWe collected a total of 151 fecal samples from 59 liver transplantation patients at different stages from the First Hospital of Shanxi Medical University. Using 16S rRNA sequencing technology, we compared the characteristics and changes of their microbiota. We selected 42 samples for metagenomic sequencing using the microPITA method to further analyze the composition and functional differences of the microbiota during the perioperative period of liver transplantation across various time points.ResultsAfter liver transplantation (LT), the diversity of gut microbiota initially decreased and then increased. Firmicutes, Proteobacteria, and Bacteroidota were the main bacterial groups during the perioperative period. Firmicutes and Proteobacteria initially decreased and then increased, while Bacteroidota exhibited the opposite process. Alpha diversity and beta diversity analyses indicated that 1 month post-transplantation was a turning point for microbiota recovery (P < 0.01). Metagenomic sequencing, analyzed using the LEfSe method, identified a total of 50 genera that played significant roles in this process. The changes in microbiota exhibited the same trend as the 16S rRNA results. KEGG pathway analysis also indicated that 1 month was a critical time point, with Ko02010 potentially being a key pathway for recovery in LT patients, and it showed a negative correlation with Bacteroidota (P < 0.05).ConclusionThe diversity of intestinal flora in the perioperative period of LT patients decreased first and then increased, and the turning point of intestinal flora recovery was 1 month after LT surgery.